2010
DOI: 10.1111/j.1601-0825.2009.01587.x
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid and orofacial clefts: a review of the evidence

Abstract: Orofacial clefts are common and burdensome birth defects with a complex genetic and environmental etiology. The contribution of nutritional factors and supplements to the etiology of orofacial clefts has long been theorized and studied. Multiple studies have evaluated the role of folic acid in the occurrence and recurrence of orofacial clefts, using observational and non-randomized interventional designs. While preventive effects of folic acid on orofacial clefts are commonly reported, the evidence remains gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(103 citation statements)
references
References 104 publications
3
97
0
3
Order By: Relevance
“…Certainly, changes in folate metabolism have been shown to affect both DNA synthesis and histone methylation during neurulation, heart development, and in diseases such as cancer (Beaudin and Stover, 2009; Momb et al, 2013; Sun et al, 2011; Tang et al, 2005; Wang et al, 2014). Folate deficiency and mutations to genes involved in the folate pathway cause orofacial defects in model vertebrates and humans (Li et al, 2011; Momb et al, 2013; Tang et al, 2005; Wehby and Murray, 2010; Wilcox et al, 2007) (Burgoon et al, 2002; Kao et al, 2014; Lee et al, 2012). However, it is less clear if these results are due to similar processes during orofacial development.…”
Section: Introductionmentioning
confidence: 99%
“…Certainly, changes in folate metabolism have been shown to affect both DNA synthesis and histone methylation during neurulation, heart development, and in diseases such as cancer (Beaudin and Stover, 2009; Momb et al, 2013; Sun et al, 2011; Tang et al, 2005; Wang et al, 2014). Folate deficiency and mutations to genes involved in the folate pathway cause orofacial defects in model vertebrates and humans (Li et al, 2011; Momb et al, 2013; Tang et al, 2005; Wehby and Murray, 2010; Wilcox et al, 2007) (Burgoon et al, 2002; Kao et al, 2014; Lee et al, 2012). However, it is less clear if these results are due to similar processes during orofacial development.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that such a benefit exists for both OFC and NTDs but that it only occurs at very high intakes of folic acid. This and other aspects of OFC and NTDs are reviewed by Wehly and Murray [14. ]…”
Section: Resultsmentioning
confidence: 99%
“…8 Smoking, alcohol consumption, and lack of vitamins during pregnancy are among the mostly studied environmental risk factors to date. [9][10][11] It is well documented that maternal smoking during pregnancy is associated with a wide variety of adverse reproductive outcomes, such as increased rates of spontaneous abortion, premature birth, smaller head size, and low birth weight (LBW) in newborns. 12,13 Among smoke products, nicotine is considered to be the main teratogenic substance that alters and delays embryonic development.…”
Section: Nicotine Exposure During Pregnancy Results In Persistent Midmentioning
confidence: 99%